Bottom-up engineering of thermoelectric nanomaterials and devices from solution-processed nanoparticle building blocks. (4th May 2017) - Ortega, Silvia; Ibáñez, Maria; Liu, Yu; Zhang, Yu; Kovalenko, Maksym V.; Cadavid, Doris; Cabot, Andreu
Abstract : Nanoparticle-based bottom-up engineered nanomaterials are extremely appealing for the direct solid-state conversion between heat and electricity. Abstract : The conversion of thermal energy to electricity and vice versa by means of solid state thermoelectric devices is extremely appealing. However, its cost-effectiveness is seriously hampered by the relatively high production cost and low efficiency of current thermoelectric materials and devices. To overcome present challenges and enable a successful deployment of thermoelectric systems in their wide application range, materials with significantly improved performance need to be developed. Nanostructuration can help in several ways to reach the very particular group of properties required to achieve high thermoelectric performances. Nanodomains inserted within a crystalline matrix can provide large charge carrier concentrations without strongly influencing their mobility, thus allowing to reach very high electrical conductivities. Nanostructured materials contain numerous grain boundaries that efficiently scatter mid- and long-wavelength phonons thus reducing the thermal conductivity. Furthermore, nanocrystalline domains can enhance the Seebeck coefficient by modifying the density of states and/or providing type- and energy-dependent charge carrier scattering. All these advantages can only be reached when engineering a complex type of material, nanocomposites, with exquisite control over structural and chemical parameters at multiple length scales. Since current conventional nanomaterial production technologies lack such level of control, alternative strategies need to be developed and adjusted to the specifics of the field. A particularly suitable approach to produce nanocomposites with unique level of control over their structural and compositional parameters is their bottom-up engineering from solution-processed nanoparticles. In this work, we review the state-of-the-art of this technology applied to the thermoelectric field, including the synthesis of nanoparticles of suitable materials with precisely engineered composition and surface chemistry, their combination and consolidation into nanostructured materials, the strategies to electronically dope such materials and the attempts to fabricate thermoelectric devices using nanoparticle-based nanopowders and inks.